Avaliação da eficiência da comunicação via rádio-frequência utilizando o transceiver nRF-24L01+ para monitoramento de sistemas elétricos no conceito de smart grid - Lacerda, Sérgio Louredo Maia (2015)
This work deals with the evaluation of the communication system by radio frequency using the NRF-24L01+® transceiver to be used in monitoring of electrical systems on the concept of smart grid. The complete system consists of one or more Units Remote Data Acquisition - URDAs; multiple Smart Sensing Units - SSUs; and Supervisory Control Subsystem - SCS. The connection between URAD and SSUs may occur via wired connection (Ethernet, RS232, USB, CAN or PLC) and wireless (RF). URADs fit to the acquisition, processing and communication of variables with low time constant while the USIs are primarily responsible for the acquisition of magnitudes with larger time constants (temperature, pressure, humidity, etc.). In this work, we focus on development and communication of SSUs. For these tests the units are of two types: a master unit, responsible for requesting data (wireless) and sending the SCS (Communication RS232, USB, CAN or RF); and a slave unit, which may account for the measured variables of interest to send to the master unit when requested. For wireless communication (RF), the transceiver nRF - 24L01+® from NORDICTM was used, because its processing characteristics and communication satisfactorily meet the needs and requirements of the project, which will be addressed in the course of this work.